The US, Strategic Environment in the South Caucasus and Armenia: A Sight on the Future - Ruben Elamiryan (Journal of Political Science: Bulletin of Yerevan University, 2022)
The political, economic and geopolitical presence of the United States in the South Caucasus dates back at least a century, when, after the First World War, they emerged as a global political, economic and geopolitical actor. Cooperation has increased dramatically since 1991, when the three countries gained independence after the collapse of the Soviet Union. From this perspective, the article focuses on identifying core US interests in Eurasia and attempting to define US strategic interests and priorities with respect to the region. In this sense, the main research question is how the US relations with the South Caucasus and in particular with Armenia will look like in the future, especially within the current stage of the Ukrainian conflict that began after February 2022.